Adolescents' Negotiations of Loyalty and Fairness in Relation to Parents' Separation Process - Grape, Lovise; Skoglund, Jeanette; Haugen, Gry Mette Dalseng; Thørnblad, Renee (Child & family social work, 2024)
Research on children's experiences of parental separation highlights equality and fairness between parents as one explanation for why children wish for symmetrical time‐sharing between parents. In this paper, we analyse adolescents' narratives and ask how adolescents negotiate closeness and distance with their parents, with a specific emphasis on issues of loyalty when adolescents' views diverge from symmetry and fairness. Narratives from qualitative interviews with 11 Norwegian adolescents aged between 12 and 17 were analysed. Ideas from the theory of invisible loyalties were applied to analyse the interviews, resulting in two topics, namely, ‘Bookkeeping of parents’ fulfilled and failed obligations’ and ‘Negotiations of obligations between parents and adolescents’. According to the adolescents in this study, fairness does not necessarily mean equal time‐sharing. Fairness is subject to negotiation, and adolescents' loyalty to parents is justified by fulfilled and failed obligations.